Guidelines on diagnostics and treatment of acromegaly (draft) - E. G. Przhiyalkovskaya; N. G. Mokrysheva; E. A. Troshina; G. A. Melnichenko; I. I. Dedov; M. B. Antsiferov; L. I. Astafieva; T. P. Bardymova; Zh. E. Belaya; G. R. Vagapova; S. Yu. Vorotnikova; A. Yu. Grigoriev; et al. (Ожирение и метаболизм, 2024)
We recommend acromegaly to be ruled in all patients with characteristic changes in appearance (A3). In all patients without characteristic changes in appearance, we recommend to rule out acromegaly, if several clinical signs suspicious for acromegaly are present (B3). We recommend acromegaly to be ruled out in all patients with pituitary adenoma (B3). We recommend to rule out acromegaly in all patients with prolactin-secreting adenomas (C4). For laboratory confirmation of acromegaly, we recommend to measure serum insulin-like growth factor-1 (IGF-1, somatomedin C) level (A3). In patients without obvious clinical signs of acromegaly and/or with a moderate increase in IGF-1 levels (IGF-1 index less than 1.3), we recommend to assess the response of somatotropic hormone (GH) to hyperglycemia (GH during an oral glucose tolerance test) (B3). In all patients with biochemically confirmed acromegaly, magnetic resonance imaging of the pituitary gland with intravenous contrast is recommended to assess pituitary adenoma size, location and growth pattern (A3). We recommend to measure blood glucose and glycated hemoglobin in all patients with confirmed acromegaly (B3). We recommend to measure serum prolactin levels in all patients with acromegaly (B3).In all patients with acromegaly and pituitary adenoma, transnasal transsphenoidal adenomectomy is recommended as first-line treatment if the patient’s consent is given and there are no contraindications (A1). For all patients with acromegaly for whom neurosurgical treatment is indicated, surgical intervention is recommended in medical centers, specializing in pituitary diseases, by neurosurgeons who perform at least 50 such operations per year (A3). We recommend that morphological and immunohistochemical examination of the removed pituitary adenoma is performed in all patients with acromegaly (A3). We do not recommend routine medical therapy for acromegaly before surgery as a mean to reduce tumor size (B2).For patients with acromegaly in whom neurosurgical treatment is not indicated or ineffective or while patient awaiting for the effect of radiation therapy, we recommend medical therapy (A1). Long-acting first-generation somatostatin analogues are recommended as first-line drug therapy for acromegaly. In case of partial/complete resistance to or intolerance to somatostatin analogs, pegvisomant is recommended as a second-line medical therapy for acromegaly (A1). We recommend starting pegvisomant from a single dose of 40–80 mg per day subcutaneously, then continue injections at a starting dose of 10 or 15 mg per day with IGF-1 monitoring after 4–6 weeks and dose adjustment if necessary (B2). In patients with acromegaly and a moderate increase in IGF-1 levels, we recommend to initiate cabergoline as medical monotherapy or, if somatostatin analogs are ineffective, in combination with them (B2).In patients with acromegaly, if the disease remains active after surgical treatment, if drug treatment is unavailable, intolerable or ineffective, and repeated neurosurgical intervention is inappropriate, it is we recommend radiation therapy (A1). A multidisciplinary approach is recommended in the management of acromegaly complications (C3).